A full-ocean-depth rated modular lander and pressure-retaining sampler capable of collecting hadal-endemic microbes under in situ conditions. (January 2019) - Peoples, Logan M.; Norenberg, Matthew; Price, David; McGoldrick, Madeline; Novotny, Mark; Bochdansky, Alexander; Bartlett, Douglas H.
Abstract: The hadal zone remains one of the least studied environments because of its inaccessibility, in part because of hydrostatic pressures extending to 110 MPa. Few instruments are capable of sampling from such great depths. We have developed a full-ocean-depth-capable lander that can be fit with sampling packages for the collection of still images, video, motile megafauna, and hadal seawater. One payload includes a pressure-retaining sampler (PRS) able to maintain seawater samples under in situ pressure during recovery. We describe the technical specifications of the lander and the PRS and preliminary results from three deployments at depths in excess of 10, 700 m in the Mariana Trench. Seawater from full-ocean depth was recovered at 81% of the in situ pressure. This facilitated the collection of microbial genomes affiliated with the family Flavobacteriaceae within the Bacteroidetes and the phylum Marinimicrobia . We show that these microbes are specifically enriched in hadal zones, representing novel trench lineages, and describe their adaptations for living in hadal environments. These findings highlight the utility of this lander system, which facilitates scientific inquiry at depths greater than 6000 m. Highlights: Description of a hadal lander capable of collecting video, megafauna, and water. Water obtained from the Mariana Trench with 81% of the in situ pressure retained. Genomes related to the Flavobacteriaceae and Marinimicrobia show hadal adaptation.